Role of fiberoptic bronchoscopy in sputum smear negative suspected cases of pulmonary tuberculosis: a study conducted in Southern part of Rajasthan - Luhadia, Atul; Luhadia, Shanti K.; Jain, Shubham; Hanfe, Mohammad Hamza; Oza, Divax; Zota, Adit; Nagda, Trishi; Shukla, Deepak; Gupta, Sujit; Saxena, Vidit; Bansal, Monica; Kankrecha, Ronak; et al. (International Journal of Research in Medical Sciences, 2020)
Background: Sputum smear negative pulmonary tuberculosis is a common problem faced by clinicians. Fiberoptic bronchoscopy may be very useful in diagnosing these cases which have no sputum or whose sputum smear is negative for acid fast bacilli. Objective of the current study was to assess the role of fiberoptic bronchoscopy in sputum smear negative under NTEP and radiologically suspected cases of pulmonary tuberculosis. Methods: Clinico-radiological suspected cases of pulmonary tuberculosis patients in whom two sputum smear for acid fast bacilli by Ziehl Neelsen stain under NTEP was negative were included in the study. Fiberoptic bronchoscopy was performed in all these patients and samples taken were sent for investigations. Results: Fiberoptic bronchoscopy was performed in 250 patients of suspected pulmonary tuberculosis whose sputum for AFB smear was negative. Cough was the most predominant symptom. Radiologically, right side disease was more common and upper zone was most commonly involved and infiltrates were common radiological finding. During bronchoscopy, congestion and hyperaemia (36%) and mucopurulent/mucoid secretions (32%) was seen in maximum number of cases. BAL was positive in 200 patients (80%), post bronchoscopy sputum was positive in 70 cases (28%) and biopsy was positive in 12 patients out of 16 performed biopsies (75%). The total TB positive cases after combining all the methods were 215 making the overall diagnostic yield of 86%. Conclusions: Fiberoptic bronchoscopy and post bronchoscopy sputum can be very useful for diagnosing sputum for AFB smear negative but clinico-radiological suspected cases of pulmonary tuberculosis patients.